Learning in the e-environment: new media and learning for the future (Libellarium: journal for research in the field of information and related sciences, 2015)
We live in times of rapid change in all areas of science, technology, communication and social life. Every day we are asked to what extent school prepares us for these changes and for life in a new, multimedia environment. Children and adolescents spend less time at school or in other settings of learning than they do outdoors or within other social communities (family, clubs, societies, religious institutions and the like). Experts must constantly inquire about what exactly influences learning and development in our rich media environment. The list of the most important life competences has significantly changed and expanded since the last century. Educational experts are attempting to predict changes in the content and methodology of learning at the beginning of the 21st century. Answers are sought to key questions such as: what should one learn; how should one learn; where should one learn; why should one learn; and how do these answers relate to the new learning environment? In his examination of the way children and young people learn and grow up, the author places special attention on the relationship between personal and non-personal communication (e.g. the internet, mobile phones and different types of e-learning). He deals with today's questions by looking back to some of the more prominent authors and studies of the past fifty years that tackled identical or similar questions (Alvin Toffler, Ivan Illich, George Orwell, and the members of the Club of Rome). The conclusion reached is that in today's world of rapid and continuous change, it is much more crucial than in the last century, both, to be able to learn, and to adapt to learning with the help of new media.
Keywords: e-learning; learning environment; multimedia; multimedia teaching; multimedia education; blended learning; hybrid learning